Xerxes : the fall of the House of Darius and the rise of Alexander - Miller, Frank, 1957- (Dark Horse Books, 2019)
The ongoing Greek rebellion against Persian tyranny reaches a turning point after the destruction of the city of Sardis and the later battle of Marathon: on a military campaign to vanquish the city of Athens and silence the Greeks once and for all, Xerxes, Persian Prince, watches as his father, King Darius, falls in battle . . . The mantle of king is passed and while his newly-inherited fleet retreats toward home, Xerxes' hatred is cemented toward Athens--and his incentive to build the Persian empire is fueled. Xerxes becomes the king of all countries--the king of Persia, ruler of Zion, and Pharoah of Egypt--and his empire is unlike any the world has ever seen, until . . . The mantle is again passed, the god king dies and Darius III continues as the king of all. But then, from the west, a tiger force strikes in Asia Minor and is on a course for collision with Persian forces. This will be the beginning of the end for Persia and the launch of Alexander the Great's rise to power!